The Difference of Results in Abdomen and Anus Area Measurement With Non-Contact Infrared Thermometer - Anna Surgean Veterini; Nancy Margarita Rehatta; Hamzah Hamzah; Widijiati Widijiati; Sarmanu Sarmanu; Subijanto Marto Soedarmo; Widodo Jatim Pudjirahardjo; Annis Catur Adi; Heni Rachmawati; I Ketut Sudiana (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2021)
Study about sepsis is chalenging to get the right therapeutic method. One clinical signs of the sepsis mice model is changes in body temperature. An easy way to examine body temperature is using infrared non-contact thermometer. The aim of this study is to compare the body temperature obtained from infrared non-contact thermometer at the abdomen and anus area. We used male Mus musculus mice, body weight of 25–30 grams, were divided into 2 groups (control and treated groups). In the control group, mice were injected with NaCl 0.9% solution, with the amount of NaCl volume equal to LPS. In the treated group, mice were injected with 2.5 mg/kgBW of LPS intraperitoneally. Body temperature measurement was measured in abdomen (tabd) and anus (tan) area. Body temperature was measured at 8th and 24th hour after LPS or NaCl injection. Body temperature value result using tabd was higher than tan. LPS injection to mice produced an increase in body temperature but was not significant when compared to the control group (8th and 24th hour). The mean difference between tabd and tan in 8th hour control groups respectively were 2.12oC. The mean difference between tabd and tan in 24th hour control groups 4.6oC. The mean difference in treated groups (8th hour) was 4.66oC, while it was 4.77oC in the 24th hour treated groups. LPS could caused vasodilation of the vessels, the measurement area of non contact-infrared thermometer will be the most important factor to be considered; tan may closer to the physiology condition.